New asymmetric N-heterocyclic-bridged mixed-valent dinuclear complexes of rhenium and ruthenium - Mellace, Maria G. (2013)
wo new mixed-metal mixed-valent complexes, of formulae: [(CO)3(bpy)ReI(bpe)RuIII(NH3)5]4+ and [(CO)3(bpy)ReI(4-CNpy)RuIII(NH3)5]4+ (where bpy=2,2′-bipyridine, bpe=trans-1,2-bis(4-pyridil)ethene, 4-CNpy=4-cyanopyridine), were prepared and characterized as solids and in acetonitrile solutions. From their spectroscopic, electrochemical and photophysical properties, the values for the reorganization energies λ and electronic coupling elements HAB for the metal-to-metal intramolecular electron transfers mediated by the N-heterocyclic bridges were calculated, using the Marcus–Hush formalism. For the 4-CNpy derivative, the reverse ruthenium-to-rhenium charge recombination—that should follow light excitation—is expected to be in the normal region, while for the bpe derivative this reaction is predicted to lie in the inverted region. The differences in redox potentials and in λ for both species account for these changes, which are relevant in the design of efficient photoconverters.